Seasonal primary production at the EPEA station, southwestern Atlantic: relationships with phytoplankton composition and environmental properties - Segura, Valeria (2025)
This study presents the first estimates of primary production (PP) from the Marine Ecological Time Series, Estación Permanente de Estudios Ambientales (EPEA) in the Argentine Sea and examines its relationship with phytoplankton community composition and environmental factors using data obtained between 2006 and 2019. Our findings indicate that PP at EPEA exhibits seasonal pulses, with an estimated annual average of 202 ± 115 g C m-2 yr-1, classifying the system as mesotrophic. The peak of PP occurred in spring associated with increased irradiance and water column stratification, and the dominance of diatoms, dinoflagellates, and haptophytes. Winter was the least productive season, characterized by low light levels and a deep mixed layer, with a prevalence of cryptophytes and ultraphytoplankton. In summer, PP was lower than in spring, and the community was dominated by picoplanktonic Synechococcus spp., adapted to low nutrients and high light. In autumn, PP increased relative to summer, associated with higher microphytoplankton biomass. A key finding was the decoupling between PP and total carbon biomass, highlighted by the high variability of the BC to ChlaS (BC/ChlaS) ratio. This ratio is crucial for linking carbon-based biogeochemical models with satellite-based PP models. Deviations from the expected seasonal patterns could point to the sensitivity of coastal PP to large-scale climate influences, such as the Southern Annular Mode (SAM) and the El Niño-Southern Oscillation (ENSO). Our results evidence the physiological adaptability of phytoplankton in this dynamic coastal environment and highlight the necessity of high-frequency sampling to improve primary productivity models in this under-sampled region.